THE ROLE OF NATIONAL VALUES IN THE FORMATION OF SPIRITUAL AND MORAL QUALITIES IN CHILDREN OF PRIMARY SCHOOL AGE (World Bulletin of Social Sciences, 2026)
The article examines the role of national values in the formation of spiritual and moral qualities in primary school children. The importance of cultural and spiritual heritage as a key factor in moral education is substantiated. The research methods include theoretical analysis of scientific literature, observation, and comparative analysis of pedagogical practices. The results show that the integration of national traditions and elements of folk culture into the educational process contributes to the development of respect, responsibility, cooperation skills, as well as patriotism and moral awareness among students. The primary school age is emphasized as a sensitive stage of moral development. The study concludes that it is necessary to actively incorporate national cultural heritage into educational practice